Pengaruh Penambahan Filler dari Selulosa Tongkol Jagung dan Zink Oksida Pada Plastik Biodegradable - Endah Rahma Danni; Abu Hasan; Robert Junaidi (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
The main objective of this research is to obtain the optimum composition of bioplastics from the main ingredients of starch, cassava husks and corncobs. In this research, cassava peel starch will be used as the basic ingredient, glycerol as a plasticizer, as well as the addition of PVA, cellulose and ZnO with different concentration variations, namely 0.4; 0.8; 1,2; 1.6 g. The manufacture of biodegradable plastic will be carried out using the melt intercalation method or phase inversion technique, namely the evaporation of the solution after the printing process on the glass plate. Then biodegradation and mechanical properties of bioplastics were tested. The results of this study obtained the optimum composition in sample D3 with the most variations in the addition of cellulose with the highest tensile strength test value of 6.008 MPa, 12% Elongation Test, 48.07% Young's Modulus, 91.6% water resistance and Estimated degradation time of 27- 34 days.